Thermally conductive electro-osmotic propulsive pressure-driven peristaltic streaming flow study with a suspended nanomaterial in a micro-ciliated tube - Butt, Adil Wahid; Akbar, Noreen Sher; Mehmood, Rashid; Farooq, Shahid (Frontiers in Materials, 2022)
This article is the study of peristaltic flow of carbon nanoparticle suspended nanofluids under the influence of electro osmosis. Flow is considered inside a vertical tube with ciliated boundary walls. Comparative study is done for single-walled carbon nanotubes and multi-walled carbon nanotubes. Exact solutions of the velocity, temperature and pressure profiles have been obtained and presented graphically. Streamlines are also plotted to visualize the difference with SWCNT and MWCNT. We found that use of CNT in the base fluid significantly enhances the thermal conductivity and helps increase the velocity of the fluid.